Dynamic Characterization of Himalayan Quartzite using SHPB. (2017) - Mishra, Sunita; Chakraborty, Tanusree; Matsagar, Vasant
Abstract: In the present work, dynamic stress-strain response of Himalayan quartzite is tested under high loading rates using split Hopkinson pressure bar (SHPB) device for the first time in the literature. The physical and static mechanical properties of quartzite e.g. dry and saturated density, specific gravity, static compressive strength and elastic modulus values are also determined. Petrological studies of quartzite are carried out through X-ray diffraction (XRD) test and scanning electron microscope (SEM) test. In the SHPB tests, it is observed from the stress-strain response that the dynamic peak stress increases with increasing strain rate whereas the elastic modulus does not show any clear trend with increase in strain rate. Dynamic force equilibrium at the incident and transmission bar ends of the rock samples is attained in all tests till the failure of the rock samples. Dynamic increase factor ( DIF ) for the rock is determined at a particular strain rate by comparing the dynamic to static peak compressive stress. Correlation equation for dynamic strength increase factor with respect to strain rate has been proposed herein.